Sexualizing the Social
XI, 228 p.
Keywords: Sociologists are increasingly aware that analyses of social life must include a consideration of how the social may be structured by the sexual. In turn, this insight is contributing to a shift in understandings of sociology. This volume - drawn from papers from the 1994 British Sociological Association Annual Conference on 'Sexualities in Social Context' - brings together a range of writers who are contributing to this exciting new agenda. Various aspects of social life - including employment, family life, representations, politics, identities and the workings of the law - are considered, in terms of how sexuality shapes their organization and they shape sexuality. In so doing a series of ongoing and new controversies and debates are confronted, from the relationship of feminism to prostitution to the constitution of the self in late modernity.